User Experience Evaluation of a Gamified Puberty Education Application Among Elementary School Students: A UEQ-Based Study - Mar'atun Ulaa; Sri Sumaryani; Yuniza Yuniza (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2026)
Background: Adolescence is a critical developmental stage marked by physical, psychological, and social changes related to puberty and reproductive health. However, many adolescents still have limited understanding of puberty, which may increase risky behaviors. Gamified digital media may provide an engaging approach to puberty education. This study evaluated the user experience of the Pubertas Cerdas application, a gamified educational platform designed for elementary school students. Method: A quantitative descriptive study with user testing was conducted among 140 elementary school students in Palembang, Indonesia. User experience was assessed using the User Experience Questionnaire (UEQ), covering attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. Data were analyzed descriptively using a scale ranging from -3 to +3. Result: The Pubertas Cerdas application demonstrated positive results across all UEQ dimensions. The highest mean score was stimulation (2.20), followed by attractiveness (2.12) and efficiency (2.05), indicating that the application was engaging, appealing, and easy to use. Perspicuity (1.95), dependability (1.88), and novelty (1.76) also showed favorable evaluations, suggesting that the application was understandable, reliable, and innovative enough for users.. Conclusion: The Pubertas Cerdas application provides a positive user experience and shows potential as a digital learning medium for puberty education among adolescents. The application may support school-based health education through interactive and accessible learning. Further development is needed to enhance the application’s innovative features and strengthen user engagement.